TEACHER STRATEGIES IN INCREASING STUDENT ACTIVITY IN E-LEARNING - I Gusti Ngurah Santika; Ni Putu Ika Putri Sujianti; I Putu Bagus Mustika (International Journal of Education and Social Science Studies, 2024)
The past year has shaken our country with the outbreak of a disease often referred to as COVID-19. In this case, educators are expected to have the skills and abilities to think creatively and innovatively to collaborate with students during the learning process. . The research aims to analyze teacher strategies for increasing student activity in e-learning for Class XI IPS at SMA Dwijendra Denpasar for the 2020/2021 academic year. This type of research is qualitative research. The data collection techniques were observation, interviews, documentation, and analysis carried out in a qualitative descriptive manner. This research was carried out at Dwijendra High School, Denpasar. Which is the subject of teachers and students. Research results (1). In this case, teachers need to be creative in collaborating with students, for example, with the material delivered using online game media. The game method is used if the teacher sees students starting to get bored, restless and not focusing on paying attention to the teacher when studying online. One of the games used is the focus game. When playing the game students look very happy and enthusiastic about participating in the game with enthusiastic voices and if when playing the game the student makes a mistake then they are punished by making the student sing and so on. (2). The teacher pays attention to students through online learning; namely, at the beginning of learning the teacher always asks if they have prayed, have they had breakfast. the teacher also always gives a smiling face. When students start to get bored with learning, the teacher also does ice-breaking and games so that students are enthusiastic and interested in participating in online learning again.